PREVALENCE OF SALMONELLA TYPHIMURIUM FROM COMMERCIAL POULTRY AND HANDLERS IN NASARAWA STATE, NIGERIA - Ibrahim, T.; Ngwai, Y. B.; Pennap, G. R. I.; Ishaleku, D.; Tsaku, P. A.; Abimiku, R. H.; Nkene, I. H.; Bassey, E. B. (FUDMA JOURNAL OF SCIENCES, 2023)
This study was designed to investigate the prevalence of Salmonella Typhimurium from commercial poultry and handlers in Nasarawa State, Nigeria. This was conducted in the Microbiology Laboratory, Nasarawa State University, Keffi, Nigeria, from 1st November 2017 to 31th April 2018. A total of 1500 samples (poultry droppings, flesh feed, handlers’ faeces and hand swabs) were screened for the presence of Salmonella Typhimurium using standard bacteriological methods. Presumptive Salmonella colonies were confirmed as serovar Typhimurium using both the conventional biochemical screening tests and Microgen Bioproduct GN identification system, and serotyping by the slide agglutination test using polyvalent antiserum according to Kauffman White’s scheme. The prevalence of S. Typhiumurium was 7.1% (106/1500), with the highest sample-related prevalence in droppings (16.7%, 50/300), the highest location-related prevalence in NW (11.8%, 59/500) and zero prevalence in hand swabs across all locations. The differences between the prevalence rates from the various sample types were insignificant (p = 0.10).The results would bridge the gaps in data of prevalence of S.Typhimurium in poultry and handlers in Nasarawa State. The Findings will be beneficial to individuals, public health officials, regulatory agencies and poultry handlers on the need for observing strict sanitation and hygienic practices in poultry rearing and processing. Salmonella Typhimurium contamination is prevalent in poultry, and handlers’ infection is possible via direct and/or indirect contact with colonized poultry